2022
DOI: 10.1186/s12913-022-08550-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of health literacy competencies on patient-centered care among nurses

Abstract: Background This study aims to identify the relationship between health literacy competencies and patient-centered care by clinical nurses. Methods The participants were 180 nurses working at three university hospitals located in G City and J Province, South Korea. Self-evaluation questionnaires were used to collect data that were collected from June 1 to 30, 2021. Data were analyzed using descriptive statistics, independent t-test, one-way ANOVA, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…As professionals, they need to improve patient health and patient-centered care by providing nursing care that facilitates literacy support. Seven studies stated that nurses have a responsibility of providing health promotion to increase patient health literacy ( 11 , 12 , 30 , 33 36 ). Health literacy is an essential factor in the scope of professional nursing practice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As professionals, they need to improve patient health and patient-centered care by providing nursing care that facilitates literacy support. Seven studies stated that nurses have a responsibility of providing health promotion to increase patient health literacy ( 11 , 12 , 30 , 33 36 ). Health literacy is an essential factor in the scope of professional nursing practice.…”
Section: Resultsmentioning
confidence: 99%
“…The quality of patient care is optimized when nurses provide care that meets their health needs, such as the need for information about the disease being suffered. Three studies found that health literacy affects healthy lifestyle behaviors, as well as improves the quality of life and care ( 11 , 31 , 36 ). Health literacy is a strategy employed by nurses to meet this need.…”
Section: Resultsmentioning
confidence: 99%
“…Person-Centered Care involves changes in the model of care, multidisciplinary teams, reconceptualizing the use of resources, new care roles, and infrastructure changes (21). From a nursing perspective, Person-Centered Care implies individualizing care, reaching care agreements, and considering and intervening in each user's specific needs, with the resulting improvement in quality (22).…”
Section: Discussionmentioning
confidence: 99%
“…Research on the COMFORT Model in clinical teaching settings has demonstrated improved self-efficacy, improved attitudes toward communication with patients and family members, and increased comfort and confidence in communicating about palliative care 6,10,11 . The COMFORT Communication App consists of eight tabs (Figure 2) promoting evidence-based nurse communication education with patients and families 12,13 . With a focus on communication skill development, Interaction Adaptation Theory serves as a conceptual lens for this usability study.…”
Section: Comfort Communication and The Appmentioning
confidence: 99%